Impact of Adiposity on Incident Hypertension Is Modified by Insulin Resistance in Adults: Longitudinal Observation From the Bogalusa Heart Study. Issue 1 (January 2016) - Zhang, Tao; Zhang, Huijie; Li, Shengxu; Li, Ying; Liu, Yaozhong; Fernandez, Camilo; Harville, Emily; Bazzano, Lydia; He, Jiang; Chen, Wei
Abstract : Adiposity and insulin resistance are closely associated with hypertension. This study aims to investigate whether the association between adiposity and hypertension is modified by insulin resistance. The cohort consisted of 1624 middle-aged normotensive black and white adults aged 18 to 43 years at baseline who followed for 16 years on average. Overweight/obesity at baseline was defined as body mass index (BMI) ≥25, and insulin resistance was measured using homeostasis model assessment of insulin resistance. Prevalence of incident hypertension was compared between the insulin-sensitive adiposity and insulin-resistant adiposity groups. The prevalence of incident hypertension was higher in the insulin-resistant adiposity than in the insulin-sensitive adiposity group (32.1% versus 22.1%, P <0.001). In multivariable logistic analyses, adjusted for baseline age, race, sex, follow-up years, and smoking, baseline insulin-resistant obesity was associated with incident hypertension (odds ratio, 1.9; P =0.008). Odds ratios did not differ between blacks and whites ( P =0.238). Of note, the odds ratios of BMI associated with hypertension significantly increased with increasing quartiles of baseline homeostasis model assessment (odds ratio, 1.3, 1.1, 1.5, and 2.5 in quartiles I, II, III, and IV, respectively; P =0.006 for trend). Slopes of increasing follow-up blood pressure with baseline BMI, measured as regression coefficients (β), were significantly greater in insulin-resistant than in insulin-sensitive individuals (β=0.74 versus β=0.35 for systolic blood pressure, P =0.004 for difference; β=0.51 versus β=0.23 for diastolic blood pressure, P =0.001 for difference). These findings suggest that insulin resistance has a synergistic effect on the obesity–hypertension association in young adults, indicating that the role of adiposity in the development of hypertension is modified by insulin resistance. Abstract : Supplemental Digital Content is available in the text.